Research-Based Learning Activity Framework with STEM Approach: Implementing Strong Dominating Set Technique in Solving Highway CCTV Placement to Enhance Students’ Metaliteracy - R. Humaizah; Dafik Dafik; I M Tirta; Z R Ridlo; Susanto Susanto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
One needed in disruptive technology is metaliteracy. It refers to literacy covering any literacy achievements especially technology and information. Its main indicators are the abilities to produce, incorporate, use, share and collaborate. Thus, higher order thinking skill is required to access these indicators by implementing the research-based learning integration with STEM approach. This research was intended to develop the research-based learning activities framework with STEM approach, namely implementing strong dominating set technique in solving the highway CCTV placement to enhance the students’ metaliteracy. The method used was narrative qualitative on developing the research-based learning activities framework integrated with STEM approach. The results were listed on a table of stages 1-6 at which each stage unraveled the learning activities.